ANALISIS SISTEM PENATAUSAHAAN BELANJA LANGSUNG DI PEMERINTAH KABUPATEN MINAHASA SELATAN (STUDI KASUS PADA DINAS SOSIAL TENAGA KERJA DAN TRANSMIGRASI) - Wonggo, Putri Marina; Affandi, Dhullo; Suwetja, I Gede (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Indirect expenditures represent expenditures that have no direct relationship to the implementation of programs and activities consisting of personnel expenditures, interest expenditures, subsidies, grants, social assistance, revenue-sharing, financial aid expenditures and unexpected expenditures. Direct expenditure is expenditure that has direct relationship with programs and activities which include personnel expenditure, goods and services expenditure and capital expenditure. Local financial management in both revenue (expenditure) and expenditure (expenditure) is very important to note, the weakness of administering the finance of this region resulted in weakness of internal financial control system, at the end will be very low quality of administrative evidence required in accounting record. The administration of regional finance is based on Permendagri number 13 of 2006 concerning the guideline of regional financial management as has been amended into Permendagri Number 59 Year 2007 and the change of the second amendment with the regulation of the Minister of Home Affairs No.21 of 2011. Target of this researchanalyze the adequacy of direct administration system in the Social Service of South Minahasa Regency based on Permendagri Number 21 of 2011.The analytical method used is descriptive analysis.The results showed that the system and procedure of direct administration administration of Social Service of Manpower and Transmigration of South Minahasa Regency has been in accordance with Permendagri Number 21 Year 2011 and the system has been adequate. However, there are still some obstacles faced such as errors of record, as well as procedural errors.Keywords : system, administration, direct spending